2014
DOI: 10.3801/iafss.fss.11-83
|View full text |Cite
|
Sign up to set email alerts
|

Enabling the Investigation of Structure Vulnerabilities to Wind- Driven Firebrand Showers in Wildland-Urban Interface (WUI) Fires

Abstract: Wind-driven firebrand showers are a major cause of structural ignition in Wildland-Urban Interface (WUI) fires. Past firebrand investigations have not been able to quantify the vulnerabilities of structures to ignition from firebrand showers, as it is difficult to develop a measurement method to replicate wind-driven firebrand attack on structures that occur in actual WUI fires. To address this problem, research has been undertaken in an intricate area involving the quantification of structure vulnerabilities … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
54
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(54 citation statements)
references
References 38 publications
0
54
0
Order By: Relevance
“…The NIST Dragon, coupled to a full-scale wind tunnel facility (Building Research Institute's in Japan), has begun to identify vulnerabilities of structures to wind-driven firebrand showers. The interested reader is directed elsewhere for recent comprehensive reviews of the NIST Dragon technology [14,16,18].…”
Section: Introductionmentioning
confidence: 99%
“…The NIST Dragon, coupled to a full-scale wind tunnel facility (Building Research Institute's in Japan), has begun to identify vulnerabilities of structures to wind-driven firebrand showers. The interested reader is directed elsewhere for recent comprehensive reviews of the NIST Dragon technology [14,16,18].…”
Section: Introductionmentioning
confidence: 99%
“…This version of the device is modified from the NIST Dragon [29][30][31][32][33][34] and consists of two parts: the main body and continuous feeding component. The feeding system was connected to the main body and was equipped with two gates to prevent fire spread (described in more detail below).…”
Section: Experimental Descriptionmentioning
confidence: 99%
“…BRI maintains one of the only full-scale wind tunnel facilities in the world designed specifically for fire experimentation, the Fire Research Wind Tunnel Facility (FRWTF). Parametric studies have been conducted using the NIST Dragon installed in BRI's FRWTF to expose roofing assemblies, building vents, siding treatments, walls fitted with eaves, and glazing assemblies to wind-driven firebrand showers [29][30][31][32][33][34]. In addition, the dangers of firebrand accumulation in front of structures have been quantified for the first time.…”
Section: Introductionmentioning
confidence: 99%
“…The tile gaps are on the order of 3 mm. Penetration of the tile gaps was not a surprise as prior work by Manzello et al [11] observed firebrands penetrating a 1 mm wire mesh. The terracotta tile roofing assembly constructed of profiled tiles (no interlocking) performed similarly to both types of concrete tiles used; namely firebrands were observed to penetrate the tiles and melt the sarking.…”
Section: Resultsmentioning
confidence: 73%
“…In these experiments, the sarking material was observed to melt, yet full penetration of the sarking material by glowing firebrands was not observed. This is important because penetration by burning firebrands could ignite materials below the sarking, such as fine fuels found in attic spaces, as shown by Manzello et al [11]. In addition, it was also not possible to conduct experiments for wind speeds larger than 10 m/s.…”
Section: Discussionmentioning
confidence: 99%